Pycnogenol Protects against Pentylenetetrazole-Induced Oxidative Stress and Seizures in Mice - Goel, Radha; Saxena, Prasoon (Current Clinical Pharmacology, 2019)
Background: Epilepsy is one of the most common and severe brain disorders in the world, characterized by recurrent spontaneous seizures due to an imbalance between cerebral excitability and inhibition. Oxidative stress is a biochemical state in which reactive oxygen species are generated and associated with various diseases including epilepsy. Pycnogenol, a polyphenol obtained from the pine tree and has antioxidant& anti-inflammatory activity. So, the aim of the study was to evaluate the effect of Pycnogenol on pentylenetetrazole (PTZ)-induced seizures in mice. Methods: The mice of swiss strain each weighing 18-30g were used. Pycnogenol (50&100mg/kg) was suspended in carboxymethyl cellulose in saline and administered orally. Diazepam (1mg/kg, i.p) was used as a standard drug. The anticonvulsant effects of the drugs were measured using PTZ and cognitive behaviour was also assessed. The biochemical estimation was done by measuring Thiobarbituric acid, Superoxide dismutase, Catalase, and reduced glutathione followed by the histopathological study. Result: Pycnogenol 50 & 100mg/kg showed a significant increase in latency to PTZ-induced seizures, decrease in duration and frequency of convulsions compared to control animals; however, the effects were dose-dependent and were more significant at a higher dose. No impairment in cognitive functions like memory and muscle relaxant was observed following pycnogenol 50 & 100 mg/kg. The effect of Pycnogenol on biochemical parameter was found to be significant. It significantly (p<0.01) decreases the level of TBARS and increases the levels of SOD, catalase, and GSH in the brain tissue. The histopathological evaluation showed less neuronal degeneration in the brain due to PTZ-induced seizures in comparison to control group. Conclusion: Thus pycnogenol has a protective approach towards convulsion and can be included as an adjuvant therapy with antiepileptic drugs.
Keywords: PTZ